Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1161/strokeaha.110.598664
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Level and Hospital-Level Determinants of the Quality of Acute Stroke Care

Abstract: Background and Purpose-Quality of care may be influenced by patient and hospital factors. Our goal was to use multilevel modeling to identify patient-level and hospital-level determinants of the quality of acute stroke care in a stroke registry. Methods-During 2001 to 2002, data were collected for 4897 ischemic stroke and TIA admissions at 96 hospitals from 4 prototypes of the Paul Coverdell National Acute Stroke Registry. Duration of data collection varied between prototypes (range, 2-6 months). Compliance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 31 publications
0
56
0
Order By: Relevance
“…Our trained interview team used the 9 The Get With The Guidelines (GWTG)-Stroke performance measures and 2 additional evidencebased interventions (antihypertensive and antidiabetic agents at discharge) 22,23 to document the care of stroke for each of the patients with acute ischemic stroke. It includes (1) intravenous recombinant tissue-type plasminogen activator in patients who arrived <2 hours after symptom onset with no contraindications; (2) antithrombotic medication within 48 hours of admission; (3) deep vein thrombosis prophylaxis within 48 hours of admission if nonambulatory; (4) counseling or medication for smoking cessation if current smoker; (5) dysphagia screening before any oral intake during hospitalization; (6) rehabilitation services during hospitalization; (7) discharge on antithrombotics among those with no contraindications; (8) discharge on anticoagulants if atrial fibrillation present among those with no contraindications; (9) discharge on statins if dyslipidemia present, low-density lipoprotein ≥100 mg/dL, or low-density lipoprotein not documented among those with no contraindications; (10) discharge on antihypertensive agents if hypertension present among those with no contraindications; and (11) discharge on antidiabetic agents if diabetes mellitus present among those with no contraindications.…”
Section: Quality Of Carementioning
confidence: 99%
“…Our trained interview team used the 9 The Get With The Guidelines (GWTG)-Stroke performance measures and 2 additional evidencebased interventions (antihypertensive and antidiabetic agents at discharge) 22,23 to document the care of stroke for each of the patients with acute ischemic stroke. It includes (1) intravenous recombinant tissue-type plasminogen activator in patients who arrived <2 hours after symptom onset with no contraindications; (2) antithrombotic medication within 48 hours of admission; (3) deep vein thrombosis prophylaxis within 48 hours of admission if nonambulatory; (4) counseling or medication for smoking cessation if current smoker; (5) dysphagia screening before any oral intake during hospitalization; (6) rehabilitation services during hospitalization; (7) discharge on antithrombotics among those with no contraindications; (8) discharge on anticoagulants if atrial fibrillation present among those with no contraindications; (9) discharge on statins if dyslipidemia present, low-density lipoprotein ≥100 mg/dL, or low-density lipoprotein not documented among those with no contraindications; (10) discharge on antihypertensive agents if hypertension present among those with no contraindications; and (11) discharge on antidiabetic agents if diabetes mellitus present among those with no contraindications.…”
Section: Quality Of Carementioning
confidence: 99%
“…3 According to our knowledge, only 3 existing studies have compared quality of stroke care between high-and low-volume institutions. One study (not restricted to stroke units) showed that higher hospital bed size was associated with better quality of stroke care, 21 whereas other studies found no direct link between volume and quality of care. 17,18 In our study, adjusting for the percentage of received processes of care had no major influence on the results.…”
Section: November 2012mentioning
confidence: 99%
“…5 The Paul Coverdell National Acute Stroke Registry found that quality of stroke care summarized as a composite of 8 performance measures varied by state in unadjusted, but not in risk-adjusted, analyses. 20 The reasons for these regional differences in GWTGStroke hospitals and other registries and programs remain unclear. Previous studies suggest that regional patterns of care, particularly for treatments such as IV-tPA, for which relatively few stroke patients are eligible, may reflect differences in hospital characteristics, such as bed capacity or teaching status; yet, we found that differences persisted after adjustment for these characteristics.…”
Section: Allen Et Al Variation In Ischemic Stroke and Tia Treatmentsmentioning
confidence: 99%